199. FAVORABLE OUTCOMES OF JEJUNAL INTERPOSITION RECONSTRUCTION WITHOUT VASCULAR ANASTOMOSIS AFTER ESOPHAGECTOMY FOR CANCER: A SINGLE-CENTER EXPERIENCE OVER TWO DECADES. (24th September 2022) - Zhao, Lilan; Pan, Xiaojie; Lin, Zhaoxian; Chen, Wenshu; Guo, Tianxing; Zhu, Lihuan; Ou, Debin
Abstract: The standard esophageal replacement after esophagectomy for cancer treatment is a gastric conduit. However, when the stomach is not available, a jejunal interposition can be performed under such circumstances. The purpose of this study was to review our experience with this technique especially without requiring microvascular anastomosis of artery or vein, and assess the surgical outcomes. We retrospectively reviewed the medical records of patients with esophageal cancer who underwent jejunum interposition without vascular anastomosis at our institution from 2003 to 2020. Data pertaining to patient characteristics, operative technique, and postoperative outcomes were collected and analyzed. Factors affecting oncologic outcomes were assessed by Kaplan–Meier estimates and Cox proportional hazards regression analyses. Postoperative quality of life were evaluated by a standard questionnaire. After 38 months of median follow-up time, 132 patients (122 males and 10 females; aged 40 to 86 years) were included. More than half of the patients (55.3%, 73/132) were above stage III. The operation time required was 294.5 ± 89.7 min, and the drainage time was 8.0 ± 5.3d. Fiveteen patients underwent cervical anastomosis. The anastomotic leakage rate was only 4.5% (6/132) among all the patients. The 90-days mortality rate was 5.3% and the overall survival at 1, 3 and 5 years were 91.7%, 76.8% and 61.8%, respectively. The prognosis was mainly correlated with tumor stage and most patients showed good quality of life. This is the largest series of jejunal interposition in a single institution from China. The nearly 20-year follow-up data suggests that, even without vascular anastomosis, the procedure using jejunum as an alternative conduit is a feasible procedure for reconstruction after esophagectomy, resulting in low morbidity and favorable prognosis.